Organ-specific regulation of growth-defense tradeoffs by plants. (February 2016) - Smakowska, Elwira; Kong, Jixiang; Busch, Wolfgang; Belkhadir, Youssef
Highlights: Resources scarcity leads to tradeoffs regulation by plants. Plant developmental programs are constrained to tradeoffs with defense systems. Small molecules hormones and light signaling regulate growth-defenses tradeoffs. The regulation of growth-defense tradeoffs in roots has so far been overlooked. Abstract : Plants grow while also defending themselves against phylogenetically unrelated pathogens. Because defense and growth are both costly programs, a plant's success in colonizing resource-scarce environments requires tradeoffs between the two. Here, we summarize efforts aimed at understanding how plants use iterative tradeoffs to modulate differential organ growth when defenses are elicited. First, we focus on shoots to illustrate how light, in conjunction with the growth hormone gibberellin (GA) and the defense hormone jasmonic acid (JA), act to finely regulate defense and growth programs in this organ. Second, we expand on the regulation of growth-defense trade-offs in the root, a less well-studied topic despite the critical role of this organ in acquiring resources in an environment deeply entrenched with disparate populations of microbes.